Transcriptomic Insights into Higher Anthocyanin Accumulation in ‘Summer Black’ Table Grapes in Winter Crop Under Double-Cropping Viticulture System - Congqiao Wang; Chengyue Li; Youhuan Li; Yue Zeng; Jie Jiang; Linhui Wu; Siyu Yang; Dan Yuan; Lifang Chen; Zekang Pei; Viola Kayima; Haidi Liu; et al. (Plants)
Anthocyanins are responsible for grape (Vitis vinifera L.) skin color. To obtain a more detailed understanding of the anthocyanin regulatory networks across’ the summer and winter seasons in grapes under a double-cropping viticulture system, the transcriptomes of ‘Summer Black’ grapes were analyzed using RNA sequencing. The average daily temperature during the harvest stage in the summer crop, ranging from 26.18 °C to 32.98 °C, was higher than that in the winter crop, ranging from 11.03 °C to 23.90 °C. Grapes from the winter crop accumulated a greater content of anthocyanins than those from the summer crop, peaking in the harvest stage (E-L38) with 207.51 mg·100 g−1. Among them, malvidin-3-O-glucoside (Mv-3-G) had the highest monomer content, accounting for 32%. The content of Cy-3-G during winter increased by 55% compared to summer. KEGG analysis indicated that the flavonoid biosynthesis and circadian rhythm—plant pathways are involved in the regulation of anthocyanin biosynthesis during fruit development. Pearson’s coefficient showed significant positive correlations between anthocyanin content and the VvDFR, VvUFGT, VvOMT, VvMYB, and VvbHLH genes in the winter crop; at full veraison stage, their expressions were 1.34, 1.98, 1.28, 1.17, and 1.34 times greater than in summer, respectively. The higher expression of VvUFGT and VvOMT led to higher contents of Cy-3-G and Mv-3-G in the winter berries, respectively.